Analisis Kemiskinan Multidimensi dan Ketahanan Pangan Provinsi Kalimantan Utara - Ainistikmalia, Nurin; Kharisma, Bayu; Budiono, Budiono (Jurnal Ekonomi dan Pembangunan Indonesia, 2022)
Poverty is multidimensional and has a close relationship with food insecurity. By using the Alkire-Foster MPI with four dimensions (monetary, health, education, basic infrastructure), it was found that the monetary dimension has a role and contributes to multidimensional poverty although it’s not the main factor. The causes of poverty are obtained from other dominant dimensions. Meanwhile, the portrait of household food security in North Kalimantan Province in aggregate has been classified into food security category. It is concluded that poverty affects food security. This study proves that multidimensional poor households are very likely to become food insecurity households.